OIL AND GOLD PRICE VOLATILITY ON INDONESIAN STOCK MARKET IN THE PERIOD OF COVID-19 PANDEMIC - Maria Magdalena Marwanti; Robiyanto Robiyanto (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2021)
The study aimed to analyze the effects of oil and gold price volatility on stock returns in Indonesia by comparing the period before and during the Covid-19 pandemic. The study took secondary data from the daily closing prices of oil (Brent and WTI), gold, and JCI. The analysis technique used was GARCH (1,1). The study found that oil and gold price volatility did not affect stock returns in the two periods. The impact of the Covid-19 pandemic on financial markets had yielded uncertain results. This finding supported the concept of gold as a safe haven during the financial crisis. The limitations in the study were focusing on the Indonesian capital market, and future research can compare the impact of the Covid-19 pandemic on developing countries with developed countries.